Commitments to Save : A Field Experiment in Rural Malawi - Brune, Lasse; Giné, Xavier; Goldberg, Jessica; Yang, Dean (2012)
This paper reports the results of a field experiment that randomly assigned smallholder cash crop farmers formal savings accounts. In collaboration with a microfinance institution in Malawi, the authors tested two primary treatments, offering either: 1) "ordinary" accounts, or 2) both ordinary and "commitment" accounts. Commitment accounts allowed customers to restrict access to their own funds until a future date of their choosing. A control group was not offered any account but was tracked alongside the treatment groups. Only the commitment treatment had statistically significant effects on subsequent outcomes. The effects were positive and large on deposits and withdrawals immediately prior to the next planting season, agricultural input use in that planting, crop sales from the subsequent harvest, and household expenditures in the period after harvest. Across the set of key outcomes, the commitment savings treatment had larger effects than the ordinary savings treatment. Additional evidence suggests that the positive impacts of commitment derive from keeping funds from being shared with one's social network.